Saltmarsh plant responses to eutrophication. Issue 8 (20th October 2016) - Johnson, David Samuel; Warren, R. Scott; Deegan, Linda A.; Mozdzer, Thomas J.
Abstract: In saltmarsh plant communities, bottom‐up pressure from nutrient enrichment is predicted to increase productivity, alter community structure, decrease biodiversity, and alter ecosystem functioning. Previous work supporting these predictions has been based largely on short‐term, plot‐level (e.g., 1–300 m 2 ) studies, which may miss landscape‐level phenomena that drive ecosystem‐level responses. We implemented an ecosystem‐scale, nine‐year nutrient experiment to examine how saltmarsh plants respond to simulated conditions of coastal eutrophication. Our study differed from previous saltmarsh enrichment studies in that we applied realistic concentrations of nitrate (70–100 μM NO3 − ), the most common form of coastal nutrient enrichment, via tidal water at the ecosystem scale ( 60, 000 m 2 creeksheds). Our enrichments added a total of 1, 700 kg N·creek −1 ·yr −1, which increased N loading 10‐fold vs. reference creeks (low‐marsh, 171 g N·m −2 ·yr −1 ; high‐marsh, 19 g N·m −2 ·yr −1 ). Nutrients increased the shoot mass and height of low marsh, tall Spartina alterniflora ; however, declines in stem density resulted in no consistent increase in aboveground biomass. High‐marsh plants S. patens and stunted S. alterniflora did not respond consistently to enrichment. Nutrient enrichment did not shift community structure, contrary to the prediction of nutrient‐driven dominance of S. alterniflora and Distichlis spicata over S. patens . Our mild responses may differ from the results of previous studies for a number of reasons. First, the limited response of the high marsh may be explained by loading rates orders of magnitude lower than previous work. Low loading rates in the high marsh reflect infrequent inundation, arguing that inundation patterns must be considered when predicting responses to estuarine eutrophication. Additionally, we applied nitrate instead of the typically used ammonium, which is energetically favored over nitrate for plant uptake. Thus, the form of nitrogen enrichment used, not just N‐load, may be important in predicting plant responses. Overall, our results suggest that when coastal eutrophication is dominated by nitrate and delivered via flooding tidal water, aboveground saltmarsh plant responses may be limited despite moderate‐to‐high water‐column N concentrations. Furthermore, we argue that the methodological limitations of nutrient studies must be considered when using results to inform management decisions about wetlands.